2019
DOI: 10.1101/522888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motion perception in the common marmoset

Abstract: words)Visual motion processing is a well-established model system for studying neural population codes in primates. The common marmoset, a small new world primate, offers unparalleled opportunities to probe these population codes in key motion processing areas, such as cortical areas MT and MST, because these areas are accessible for imaging and recording at the cortical surface. However, little is currently known about the perceptual abilities of the marmoset. Here, we introduce a paradigm for studying motion… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 61 publications
(25 reference statements)
5
15
0
Order By: Relevance
“…Uncertainty-guided exploration also predicts that exploratory choices, and consequently lapses, should decrease with training as the animal becomes more certain of the rules and expected rewards, explaining training-dependent effects on lapses in our rats ( Figure 3—figure supplement 2g, right) and similar effects reported in primates ( Law and Gold, 2009 ; Cloherty et al, 2019 ). This can also potentially explain why children have higher lapse rates ( Witton et al, 2017 ; Manning et al, 2018 ), as they have been shown to be more exploratory in their decisions than adults ( Lucas et al, 2014 ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Uncertainty-guided exploration also predicts that exploratory choices, and consequently lapses, should decrease with training as the animal becomes more certain of the rules and expected rewards, explaining training-dependent effects on lapses in our rats ( Figure 3—figure supplement 2g, right) and similar effects reported in primates ( Law and Gold, 2009 ; Cloherty et al, 2019 ). This can also potentially explain why children have higher lapse rates ( Witton et al, 2017 ; Manning et al, 2018 ), as they have been shown to be more exploratory in their decisions than adults ( Lucas et al, 2014 ).…”
Section: Discussionsupporting
confidence: 78%
“…right) and similar effects reported in primates (Law and Gold, 2009;Cloherty et al, 2019). This can also potentially explain why children have higher lapse rates (Witton, Talcott, and Henning, 2017;Manning et al, 2018), as they have been shown to be more exploratory in their decisions than adults (Lucas et al, 2014).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Recent research has also confirmed that marmosets can be trained to perform a wide range of visual, oculomotor and cognitive tasks while head restrained, in a manner comparable to macaques and humans (Mitchell et al 2014Johnston et al 2019;Cloherty et al 2020). The marmoset brain also has major advantages over rodents and other primate models for neurophysiological research.…”
Section: Introductionmentioning
confidence: 87%
“…The last key prediction of the ideal observer model is that performance should asymptote at 0 and 1 for very easy stimuli. However, in practice this is often not the case, as has been observed in a large number of psychophysical studies in humans (Treutwein and Strasburger, 1999;Klein, 2001;Wichmann and Hill, 2001;Flesch et al, 2018;Mihali et al, 2018), nonhuman primates (Law and Gold, 2009;Cohen and Maunsell, 2009;Cloherty et al, 2019), mice (Busse et al, 2011;Burgess et al, 2017;Odoemene et al, 2018;Pinto et al, 2018;Wang et al, 2018;Lak et al, 2018) and rats (Raposo et al, 2012;Brunton, Botvinick, and Brody, 2013;Scott et al, 2015;Nikbakht et al, 2018;Piet et al, 2017;Mendonca et al, 2018). These deviations in the asymptotes are known as lapses, since they are assumed to arise from occasional lapses in attention, or errors in motor execution (Wichmann and Hill, 2001).…”
Section: Lapsesmentioning
confidence: 98%